Essentials of gifted assessment - Pfeiffer, Steven I. (Hoboken, New Jersey John Wiley & Sons, Inc., 2015)
"A comprehensive guide to identifying and supporting uniquely bright and talented learners. Early identification and intervention greatly benefits gifted students who may otherwise never realize their full potential. Essentials of Gifted Assessment is an evidence-based overview of what makes students gifted, how giftedness is best identified, and strategies for promoting achievement in high-ability students"--Back cover.
Introduction to gifted assessment -- Conceptions of giftedness guide gifted assessment -- Gifted assessment : guiding principles and fundamental beliefs -- Measuring intellectual and academic ability -- Identifying and assessing creativity -- Alternative gifted assessment methods -- Frequently asked questions about gifted assessment.
Includes bibliographical references (pages 143-161) and index.
Keywords: Gifted children -- Identification; Gifted children -- Education